GEOMETRY IN WARLI: MERGING FOLK ART WITH MATHEMATICS TEACHING - Sharma, Anjali; Singh, Sukanya; Kumar, Vikash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study was themed on art integration (folk art “Warli” and geometry images) in mathematics teaching and its effect on learners’ achievement. The objectives were (i) to develop art-integrated mathematical instructional modules to teach mathematical concepts and (ii)To measure the effect of an art-integrated mathematical instructional intervention on learner achievement. The quasi-experimental post-test research design with a single group post-test design was used. 45 participants of 7th-grade students from Govt Upper Primary School have been selected. The intervention was designed on the Triangle and its Properties through Warli folk art and geometry images. After obtaining post-test scores, data analysis was done. Therefore, learners’ overall achievement was based on learning outcomes. The results revealed that the range of achievement was between 60-95%, and achievement of remembering, understanding, and applying learning objectives was 89%, 83%, and 84%, and analyzing learning outcomes achieved 64% while evaluating and creating learning outcomes were committed to 63 % and 69 %. The results showed that the art-integrated instructional intervention was found to be positive in higher-order cognitive abilities.